1995
DOI: 10.1177/107769909507200104
|View full text |Cite
|
Sign up to set email alerts
|

The Sound Bites, the Biters, and the Bitten: An Analysis of Network TV News Bias in Campaign ′92

Abstract: This study pulls together two separate lines of research — sound bite research and news bias research — within a single Campaign ′92 network TV news study. Presidential and vice presidential campaign stories that appeared on network television were analyzed in terms of categories of biters and types of bites. Results indicated that the twenty-year trend of shrinking sound bites has stopped. Contrary to statements made by some members of the working press, there was no evidence of liberal news bias in the netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 0 publications
1
11
0
2
Order By: Relevance
“…There was a potentially meaningful advantage in coverage for the Democratic candidate only in 1992. Similar conclusions about the 1992 campaign coverage have been reached by other scholars Lowry & Shidler, 1995). Whether particular patterns of candidate coverage were related to elites' claims of media bias during the course of these campaigns was the focus of our analysis.…”
Section: Valence Coveragesupporting
confidence: 71%
“…There was a potentially meaningful advantage in coverage for the Democratic candidate only in 1992. Similar conclusions about the 1992 campaign coverage have been reached by other scholars Lowry & Shidler, 1995). Whether particular patterns of candidate coverage were related to elites' claims of media bias during the course of these campaigns was the focus of our analysis.…”
Section: Valence Coveragesupporting
confidence: 71%
“…For example, research about the hostile media effect has found that greater levels of partisanship results in more perceived media bias (Gunther & Schmitt, 2004;Vallone, Ross, & Lepper, 1985). Attributes of media content have also been examined in an effort to understand how these qualities influence perceptions of media bias (Lowry & Shidler, 1995;Smith, 2010). Additionally, Eveland and Shah (2003) proposed that interpersonal factors might affect perceptions of media bias, finding that more conversation with like-minded others was related to greater individual perceptions of media bias.…”
Section: Media Bias and Third-person Perceptionmentioning
confidence: 99%
“…Then, using balance as a baseline, they declare a bias in favor of the candidate toward which the count is slanted. For example, Lowry and Shidler (1995) explicitly charge the three networks with liberal bias in 1992 after discovering that almost twice as many negative sound bites were aired by Republicans about the Bush ticket than by Democrats about the Clinton ticket. They argue that, as advocates for each candidate (i.e., aides or congressional allies) are always readily available to give a sound-bite-worthy comment, the editorial choice to use some more than others results from reporters seeking sources who "confirm their prior biases" (pp.…”
Section: Problems With the Balance Baselinementioning
confidence: 98%